Development of Knowledge and Attitudes Survey on Pain Management for Korean Long-term Care Professionals - So-Hi Kwon; Hyunsim Kim; Seurk Park; Wooseok Jeon (Elsevier, 2020)
Purpose: Inappropriate knowledge and attitude toward pain management of professionals has been pointed to be major obstacles to effective pain management in long-term care setting. The purpose of this study was to develop the knowledge and attitudes survey on pain management for Korean long-term care (LTC) professionals (KASP-K). Methods: To develop the KASP-K, the knowledge and attitudes survey regarding pain developed by Ferrell and McCaffery in 2014 was amended after a review of broad literature and the latest pain management standards. A rigorous validation process of the KASP-K was performed by testing the content validity, item difficulty and discrimination index, construct validity, test-retest reliability, and internal consistency. Results: The KASP-K consisted of 22 items and showed a content validity index of >0.7. The average difficulty of the KASP-K was 0.56 and the discrimination index was >0.2. The construct validity of the KASP-K was verified because of the differences in the sum scores depending on pain education (t = 2.30, p = .024). The test-retest reliability was r = .79 (p < .001) and the Cronbach's alpha was 0.73. Conclusion: This preliminary evaluation of the KASP-K demonstrated acceptable validity and reliability. The KASP-K will be able to provide scientific and empirical data regarding the knowledge of and attitude toward pain management by LTC professionals.